Structure and Composition of Weed In Corn Fields (Zea mays L.) Village Belayu Marga District Tabanan Regency Bali Province - Zulfa, Risqa Izzatul; Joni, Martin; Wijaya, I Made Saka (Metamorfosa: Journal of Biological Sciences; Vol 10 No 1 (2023)DO - 10.24843/metamorfosa.2023.v10.i01.p05, 2023)
Corn ( Zea mays L.) is one of the most important carbohydrate-producing food crops in the world. One of the problems in corn production is a decrease in the quantity and quality of corn due to the presence of weeds that grow around corn fields. This study aims to determine the structure and composition of weeds in the corn fields of Belayu Village, Marga District, Tabanan Regency, Bali Province. The method used in this study is the permanent quadrat method with plot size 1x1 m. Data were analyzed using vegetation parameters consisting of Important Value Index (IVI), diversity index (H'), dominance index (C), evenness index (E), and similarity index (IS). The results obtained were the composition of weeds found in the 3 rd week, namely 18 species from 9 families, at the 6 th week, 25 species from 16 families, and at the 9 th week, 31 species from 19 families. The highest IVI values ??were found in Cyperus rotundus L of the Cyperaceae families at the 3 rd , 6 th , and 9 th weeks. Biodiversity (H') index is moderate ranges from 2.29 to 2.77, the dominance index (C) indicates that no weeds dominate with values ??ranging from 0.09-0.13 The evenness index (E) indicates that the species Weed types were classified as evenly distributed with values ??ranging from 0.78-0.80, and a similarity index (IS) of 72.9%, indicating that the similarity of weed species in each category was classified as high.